2001
DOI: 10.2174/0929867013373417
|View full text |Cite
|
Sign up to set email alerts
|

The Design, Structure, and Therapeutic Application of Matrix Metalloproteinase Inhibitors

Abstract: Matrix metalloproteinases (MMPs) are a family of zinc-containing enzymes involved in the degradation and remodeling of extracellular matrix proteins. The activities of these enzymes are well regulated by endogenous tissue inhibitors of metalloproteinases (TIMPs). Chronic stimulation of MMP activities due to an imbalance in the levels of MMPs and TIMPs has been implicated in the pathogenesis of a variety of diseases such as cancer, osteoarthritis, and rheumatoid arthritis. Thus, MMP inhibitors are expected to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
144
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(153 citation statements)
references
References 91 publications
(139 reference statements)
1
144
0
8
Order By: Relevance
“…9 phosphonic and phosphinic acid [92]. However, since they rely in zinc chelating for activity, a poor selectivity towards MMPs have been observed [93] and disappointing results have been obtained for most compounds except phosphinic acids (reviewed by [11]).…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…9 phosphonic and phosphinic acid [92]. However, since they rely in zinc chelating for activity, a poor selectivity towards MMPs have been observed [93] and disappointing results have been obtained for most compounds except phosphinic acids (reviewed by [11]).…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…Other zinc-binding ligands that have been utilized include reverse hydroxamic acids, carboxylic acids, thiols, and thiadiazoles (Skiles et al, 2001). Tryptophane-based biphenylsulphonamide matrix metalloproteinase inhibitors were synthesized, evaluated in vitro; in vivo and as imaging agent and were published previously (Oltenfreiter et al, 2004(Oltenfreiter et al, , 2005a.…”
Section: Introductionmentioning
confidence: 99%
“…Structural changes made to the biphenyl ring system, the α-position to carboxylic acid and the carboxylate moiety, have an influence on biological activity (O'Brien et al, 2000). Earlier experiments and SAR studies showed that biphenylsulfonamides substituted with bromine in the 4'-position significantly improved the in vitro activity and exhibited superior pharmacokinetics (C max , t 1/2 , AUCs) relative to the compounds without bromine (Skiles et al, 2001). Halogens appended to the 4'-position of the * Supported by EU Grant LSHC- CT-2003-503297 'cancerdegradome'. biphenyl ring, in general, increased potency against some MMPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it was speculated that an improvement in the selectivity toward a specific MMP and a better understanding of the disease would produce useful treatments in the future. 8 As a result, a large number of low nanomolar MMP inhibitors with improved selectivity were synthesized, but their applicability in the clinic has not yet been proven. 9 Therefore, there is still a need for new strategies to develop MMP inhibitors that avoid side effects and make MMPs druggable targets.…”
mentioning
confidence: 99%